PTX3 Polymorphisms Influence Cytomegalovirus Reactivation After Stem-Cell Transplantation - Campos, Cláudia F.; Leite, Luís; Pereira, Paulo; Vaz, Carlos Pinho; Branca, Rosa; Campilho, Fernando; Freitas, Fátima; Ligeiro, Dário; Marques, António; Torrado, Egídio; Silvestre, Ricardo; Lacerda, João F.; et al. (Frontiers in Immunology, 2019)
Background: Reactivation of latent human cytomegalovirus (CMV) in patients undergoing allogeneic stem-cell transplantation (HSCT) predisposes to several clinical complications and is therefore a major cause of morbidity and mortality. Although pentraxin-3 (PTX3) has been previously described to bind both human and murine CMV and mediate several host antiviral mechanisms, whether genetic variation in the PTX3 locus influences the risk of CMV infection is currently unknown. Methods: To dissect the contribution of genetic variation within PTX3 to the development of CMV infection, we analyzed described loss-of-function variants at the PTX3 locus in 394 recipients of HSCT and their corresponding donors and assessed the associated risk of CMV reactivation. Results: We report that the donor, but not recipient, h2/h2 haplotype in PTX3 increased the risk of CMV reactivation after 24 months following transplantation, with a significant effect on survival. Among recipients with h2/h2 donors, CMV seropositive patients as well as those receiving grafts from unrelated donors, regardless of the CMV serostatus, were more prone to develop viral reactivation after transplantation. Most importantly, the h2/h2 haplotype was demonstrated to display an influence toward risk of CMV reactivation comparable to that conferred by the unrelated status of the donor alone. Conclusions: Our findings demonstrate the important contribution of genetic variation in donor PTX3 to the risk of CMV reactivation in patients undergoing HSCT, highlighting a promising prognostic value of donor PTX3 to predict risk of CMV reactivation in this clinical setting.